Is e-cigarette advertising associated with e-cigarette use among young people? New survey evidence from Poland - Świątkowska, Beata; Zajdel, Radosław; Balwicki, Łukasz; Kaleta, Dorota (Frontiers in Public Health, 2024)
Objective: Young people are routinely exposed to e-cigarettes advertising. We examined the impact of e-cigarette advertising on e-cigarette use in a large representative sample of adolescents. Methods: Data came from cross-sectional sample of the nationwide study on the health effects of tobacco products called PolNicoYouth, which included adolescents aged 15–18 years (N=7,498). Data were collected through a detailed questionnaire recommended by international health organizations for monitoring tobacco use by adolescents. Simple and multiple logistic regression analyzes were conducted, adjusting for sex, age, type of school, place of residence, smoking of traditional cigarettes and parental smoking. Frequencies and proportions for descriptive statistics, and adjusted odds ratios with 95% confidence intervals for logistic regression models were reported. Results: Approximately, 56% of interviewees had noticed some form of e-cigarettes advertising. Exposure to e-cigarette advertising was significantly associated with ever use of e-cigarettes (OR=1.29; 95% CI: 1.09–1.53). Exposure to e-cigarette advertising via club/pub/disco was significantly associated with current e-cigarette use (OR=1.58; 95% CI: 1.06–2.36). Adolescents who have ever used e-cigarettes were more likely than never users to report exposure to advertisements on club/pub/disco (OR=1.57; 95% CI: 1.08–2.30) and internet (OR=1.22; 95% CI: 1.01–1.47). Conclusions: Despite the applicable advertising restrictions, the majority of young people declared contact with e-cigarette advertising, which shows the urgent need for more global action. The internet and advertisements in clubs, pubs and discos seem to be the key places of exposure. These forms of exposure need to be urgently addressed given their clear link to e-cigarette use.